Digital Vigilantism and Its Compatibility with Criminal Justice Principles in Indonesia - Ayu, Hanuring (Eastasouth Institute, 2025)
Digital vigilantism, the act of individuals taking justice into their own hands through online platforms, has become increasingly prevalent in Indonesia. This phenomenon often arises in response to perceived inefficiencies or corruption in the formal legal system, where individuals bypass the judicial process to punish wrongdoers. This paper analyzes the compatibility of digital vigilantism with Indonesia's criminal justice principles, focusing on key legal norms such as due process, the right to a fair trial, and the rule of law. Through a normative legal analysis, this study evaluates how digital vigilantism conflicts with these principles, particularly in the context of Indonesian law. The findings reveal that while digital vigilantism is driven by a desire for justice, it undermines fundamental rights such as the presumption of innocence and the right to a fair trial. The research highlights the need for legal reforms that address the rise of digital vigilantism while ensuring that individual rights are safeguarded and justice is delivered through formal legal channels. It concludes that although digital platforms have become a space for public discourse, they should not replace the judicial system, and legal reforms are necessary to balance the interests of justice and individual rights.